Application of the Green Building Concept (BGH) in High-Rise Office Buildings Based on Hybrid Dynamics to Improve Cost Performance - Barri, Ahmad Barri; Budiandru (International Journal of Science and Society, 2024)
Global warming, including droughts, rising sea levels, melting polar ice caps, and solar storms, poses a very serious and significant threat to the planet due to current climate change. Green Buildings (GB) are buildings that achieve significant and measurable results in saving energy, water, and other resources by applying BGH principles based on the function and classification of the project. The Indonesian government's latest regulation, through the Technical Guidance on BGH Performance Evaluation Standards of the Ministry of Public Works and Public Housing (PUPR) for 2022, is a way to reduce carbon emissions and achieve the net zero emissions (NZE) target by 2060. Regulatory Review: This study aims to analyze the factors that most influence the implementation of green buildings by the Minister of Public Works and Public Housing ministry of high-rise office buildings in indonesia towards increasing costs using the hybrid dynamic method, using Structural Equation Modeling (SEM) - Partial Least Square (PLS).